The Kansas Beef Industry - Wood, Charles L. (University Press of Kansas, 1980)
This book relates the modern development of the Kansas beef cattle industry, combining both the history of production-including specific business problems and the significant work in upbreeding-and an examination of the marketing aspects of the industry that became so important during the twentieth century. Sharpest focus is on the period 1890 to 1940, after the Western beef industry had passed through the transition from using the expansive, openrange method of beef production to the more rational and organized methods of today.